On the drought in the Balearic Islands during the hydrological year 2015–2016 - C. Ramis; R. Romero; V. Homar; S. Alonso; A. Jansà; A. Amengual (Natural Hazards and Earth System Sciences, 2017)
During the hydrological year 2015–2016 (September to August) a severe drought affected the Balearic Islands, with substantial consequences (alleviated partially by desalination plants) on water availability for consumption from reservoirs and aquifers and also on the vegetation cover. In particular, a plague of Xylella fastidiosa reached an alarming level for almond and olive trees. The expansion of this infestation could be attributed to, or at least favored by, the extreme drought. In this paper we analyze this anomalous episode in terms of the corresponding water balance in comparison with the balance obtained from long-term climatological data. It is shown that the drought was the result of a lack of winter precipitation, the lowest in 43 years, which led to a shortage of water storage in the soil. In several meteorological stations analyzed, evaporation was greater than precipitation during all the months of the year. In terms of attribution, it is found that during the 2015–2016 winter the atmospheric circulation over the North Atlantic was largely westerly and intense, with high values of the NAO index that were reflected in high pressures over the Iberian Peninsula and the western Mediterranean.